SNLS data are consistent with acceleration at z≈3 - Amendola, Luca; Gasperini, Maurizio; Piazza, Federico (Arxiv, 2006)
We point out that the Type Ia supernovae in the SNLS dataset are consistent with an early beginning of the cosmic acceleration if dark energy interacts strongly with dark matter. We find that the acceleration could have started at redshift z =3 and higher.